Maqashid Syariah Approach on the Empowerment of Human Resources in Mulyodadi village Bantul Yogyakarta - syamsuri syamsuri syamsuri (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
The process of community economic development by involving the community directly from planning, implementation to evaluation is a model of empowerment that raises human dignity on the real essence. The villagers is not only an object of development, but every individual is required to be involved in the whole process of empowerment. However, in its implementation there are many obstacles, then this article tries to analyze the inhibiting factors as well as solutions of empowerment program of Human Resources in Mulyodadi village. Mulyodadi was selected as a research sample, because of agricultural typology and eco-cultural tourism that developed well. By using qualitative method and taking data through interview, observation, and documentation (triangulation). Finally this article found two factors inhibiting the empowerment of human resources that is internal and external aspects. However, these two factors can be solved with some solutions and approaches made by the government and the community.